Synthesis of N‐Heterocycles via Oxidant‐Free Dehydrocyclization of Alcohols Using Heterogeneous Catalysts - Sun, Kangkang; Shan, Hongbin; Lu, Guo‐Ping; Cai, Chun; Beller, Matthias (Angewandte Chemie International Edition, 2021)
N‐Heterocycles, such as pyrroles, pyrimidines, quinazolines, and quinoxalines, are important building blocks for organic chemistry and the fine‐chemical industry. For their synthesis, catalytic borrowing hydrogen and acceptorless dehydrogenative coupling reactions of alcohols as sustainable reagents have received significant attention in recent years. To overcome the problems of product separation and catalyst reusability, several metal‐based heterogeneous catalysts have been reported to achieve these transformations with good yields and selectivity. In this Minireview, we summarize recent developments using both noble and non‐noble metal‐based heterogeneous catalysts to synthesize N‐heterocycles from alcohols and N‐nucleophiles via acceptorless dehydrogenation or borrowing hydrogen methodologies. Furthermore, this Minireview introduces strategies for the preparation and functionalization of the corresponding heterogeneous catalysts, discusses the reaction mechanisms and the roles of metal electronic states, and the influence of support Lewis acid–base properties on these reactions. This Minireview summarizes recent developments in which both noble and non‐noble metal‐based heterogeneous catalysts are used to synthesize N‐heterocycles from alcohols and N‐nucleophiles via acceptorless dehydrogenation or borrowing hydrogen methodologies. The strategies for the preparation and functionalization of heterogeneous catalysts, reaction mechanisms, and the roles of heterogeneous catalysts in these reactions are also discussed.